2007
DOI: 10.1091/mbc.e07-02-0138
|View full text |Cite
|
Sign up to set email alerts
|

Two Alternative Mechanisms That Regulate the Presentation of Apoptotic Cell Engulfment Signal inCaenorhabditis elegans

Abstract: Phosphatidylserine exposed on the surface of apoptotic mammalian cells is considered an "eat-me" signal that attracts phagocytes. The generality of using phosphatidylserine as a clearance signal for apoptotic cells in animals and the regulation of this event remain uncertain. Using ectopically expressed mouse MFG-E8, a secreted phosphatidylserinebinding protein, we detected specific exposure of phosphatidylserine on the surface of apoptotic cells in Caenorhabditis elegans. Masking the surface phosphatidylserin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
117
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(120 citation statements)
references
References 48 publications
3
117
0
Order By: Relevance
“…PS, which is normally restricted to the inner leaflet of the plasma membrane, is externalized during apoptosis and serves as an eat me signal to trigger phagocytosis (Fadok et al 1992a;Martin et al 1995;Fadok et al 1998). PS exposure on the surface of apoptotic cells in C. elegans has been shown to be a conserved apoptotic event and is important for removal of apoptotic cells (Venegas and Zhou 2007;Wang et al 2007;Zullig et al 2007). Interestingly, both WAH-1 and its human homolog AIF, the proapoptotic factors critical for nuclear DNA degradation, are also involved in promoting PS externalization in apoptotic cells (Susin et al 1999;Wang et al 2007).…”
Section: Cell Death Executionmentioning
confidence: 99%
See 3 more Smart Citations
“…PS, which is normally restricted to the inner leaflet of the plasma membrane, is externalized during apoptosis and serves as an eat me signal to trigger phagocytosis (Fadok et al 1992a;Martin et al 1995;Fadok et al 1998). PS exposure on the surface of apoptotic cells in C. elegans has been shown to be a conserved apoptotic event and is important for removal of apoptotic cells (Venegas and Zhou 2007;Wang et al 2007;Zullig et al 2007). Interestingly, both WAH-1 and its human homolog AIF, the proapoptotic factors critical for nuclear DNA degradation, are also involved in promoting PS externalization in apoptotic cells (Susin et al 1999;Wang et al 2007).…”
Section: Cell Death Executionmentioning
confidence: 99%
“…Externalization of PS on the cell surface is a hallmark of apoptosis; exposed PS is a conserved eat me signal that triggers phagocytosis in many organisms, including C. elegans (Fadeel and Xue 2009). Using a secreted PS-binding protein GFP fusion such as the Annexin V::GFP fusion (sAnxV::GFP), the MFG-E8::GFP, or the secreted GFP::lactadherin fusion (sGFP::Lact C1C2 ) as a PS sensor; exposed PS is detected on the surface of apoptotic cells in C. elegans (Fadok et al 2001;Venegas and Zhou 2007;Wang et al 2007;Zullig et al 2007;Mapes et al 2012;Zhang et al 2012).…”
Section: Presentation Of Eat Me Signalsmentioning
confidence: 99%
See 2 more Smart Citations
“…Phosphatidylserine exposure on the outer membrane leaflet is a conserved feature of apoptosis, and recognized by mammalian macrophage and during corpse engulfment in C. elegans. [16][17][18][19] The so-called psr gene was identified by expression-cloning the target of an engulfment-blocking antibody, 20 but is now thought to encode a nuclear protein, and recent studies have convincingly demonstrated that it is not required for corpse engulfment by either mouse fibroblasts or Drosophila hemocytes. 21,22 Meanwhile, other mechanisms of recognizing phosphatidylserine have been uncovered in mammals.…”
Section: Eat To Competementioning
confidence: 99%